Seasonal and diel patterns in singing activity of humpback whales migrating through Bermuda - Narganes Homfeldt, Tamara; Risch, Denise; Stevenson, Andrew; Henry, Lea-Anne (Frontiers in Marine Science, 2022)
Humpback whales (Megaptera novaeangliae) produce song and non-song vocalisations, which allows their presence to be detected through passive acoustic monitoring. To determine the seasonal and diel acoustic presence and acoustic behaviour of humpback whales at the migratory stopover site off Bermuda, three hydrophones were deployed between March 2018 and April 2019 on Challenger Bank and the Bermuda platform. Song was the predominant vocalisation type encountered, with 65% of song recordings containing whale chorus and a clear seasonal trend of humpback whale occurrence in the spring and winter months from late December to mid-May. A strong diel pattern in singing activity was detected. Singing activity significantly increased at night relative to the daytime (p<0.01), whilst twilight periods were characterised by intermediate levels of singing. The song structure encountered in spring 2018 consisted of 18 units, 6 themes and 5 transitional phrases. The high occurrence of whale chorus and the strong seasonal and diel patterns of male humpback whale singing activity highlights the importance of Bermuda not just on their northward migration during spring, as described historically, but also on their southward migration during winter. Bermuda therefore constitutes a two-way migratory stopover site for humpback whales. The present study also provides Bermuda’s planning authorities with better constraints on the duration and intensity of anthropogenic activities in these waters.